Biomechanical analysis of successful and unsuccessful snatch lifts in elite female weightlifters - Mastalerz, A.; Szyszka, P.; Grantham, W.; Sadowski, J. (Journal of Human Kinetics, 2019)
The aim of this study was to identify biomechanical factors affecting successful and unsuccessful snatch attempts in elite female weightlifters during the 2013 World Weightlifting Championships. Fourteen female competitors took part in this study. Their successful and unsuccessful snatch lifts with the same load were recorded with 2 camcorders (50 Hz), and selected points were digitized manually on to the body and the barbell using the Ariel Performance Analysis System. The kinetic and kinematic barbell movement as well as the athlete`s body movement variables during the liftoff phase were examined. The results of this study show statistical differences (p = 0.05) between successful and unsuccessful attempts in relation to the angle values in the knee and hip joints in preparation for the aerial phase position. Similarly, the center of gravity velocity was significantly higher in successful attempts during the catch phase. Thus, coaches should pay particular attention to the accuracy of the execution in preparation for the aerial phase position and to the velocity of the center of gravity of the competitors during the catch phase.